What are the behaviours toward covid-19 among the Gazan community? An online cross-sectional survey, Palestine (Al-Quds Journal for Natural Sciences, 2022)
Abdelraouf A. Elmanama 1, Adnan I. Al-Hindi 1,*, Mariam R. Al-Reefi 21, *Medical Laboratory Sciences Department, Faculty of Health Sciences, Islamic University of Gaza, B.O.Box 108, Gaza, Palestine.2 Faculty of Science, Al-Esraa University, Gaza, PalestineAbstractCovid-19 is one of the contagious diseases and started in December 2019, then became pandemic. The current study aimed to measure the knowledge, attitudes, and practices towards COVID-19 among the Palestinian community through online cross-sectional survey. This cross-sectional study was conducted during the period 10th of May 2020 to 28th of Sep 2020. In this survey five hundred forty subjects agreed to participate and fill the whole questionnaire. The questionnaire consisted of four main themes: 1) demographics, 2)knowledge about corona virus, 3) attitudes toward corona virus; and 4) The final section of the questionnaire assessed the participants’ practices. The overall knowledge score was classified to 68.4%, 86.7% as good knowledge, and 13.3% as un-proper knowledge. The results showed that the major age of the respondents was between 18-30 years old (50.2%) while the majority of the participants were of university education level (66.3%). The total participants were 541 348 (64.3%) were females and 193 (35.7%) were males. Only 24.8% believed that they should wear a mask and/or gloves when leaving their home and 41.9% thought they should take antibiotics daily to avoid being infected. It is concluded that Palestinians had a considerable knowledge about COVID-19, and a positive attitude towards using protective measures, which is important to limit the spread of the disease and understanding the attitude of the public towards the disease.